The Contribution of Social Science Learning in Creating The Social Behavior of Four Grade Students at SD Negeri 2 Ukir (as Inclusion School) at Sale Distric, Rembang Regency - Windrianingsih, Sinta Selvi; Utomo, Cahyo Budi; Sanjoto, Tjaturahono Budi (JESS (Journal of Educational Social Studies), 2018)
Social behavior in talent and nature gift is different for every student’s, either normal child or special child. One of ways in creating social behavior is doing social science learning. SD Negeri 2 ukir is one of schools that is pointed by government of Rembang to be inclusion school. Therefore, this research is done in order to evaluate the social science learning activity, the social behavior of four grade students, and also the contribution of social science learning in creating the social behavior of four grade students of SD Negeri 2 Ukir. The aims of the study are to describe and analyze the process of social science learning, social behavior and the contribution of social l science learning in creating social behavior of four grade students of SD Negeri 2 Ukir. The research method of this research is qualitative approach. The result of this research showed that the social science learning in four grade at SD Negeri 2 Ukir used KTSP and lesson plan which were modified as the students need. In general social behavior in this school is good enough. Factors that student’s social behavior comes from family environment and school environment. The contribution of social science learning in creating the social behavior is teaching the students the value of social science such as honest behavior, responsibility, caring, manner, curiosity, respect and self- confident. The conclusion of this research showed that the contribution of social science learning in creating the social behavior of four grade students of SD Negeri Ukir 2 in general is in good category.